Oxford Handbooks Online 2016
DOI: 10.1093/oxfordhb/9780190219000.013.19
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Organizational Citizenship

Abstract: In this chapter, we provide a detailed examination of the relationship between employee justice perceptions and organizational citizenship behavior OCB. Beginning with the earliest research on OCB, we articulate how these two topics within organizational sciences developed alongside one another as researchers attempted to articulate not only what kinds of justice would influence extra-role behaviors but also how those effects emerge. We also discuss modern trends in the study of justice and OCB, examining new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 0 publications
1
56
1
1
Order By: Relevance
“…Our results support the assumption that the fairness perceptions of employees, particularly regarding treatment by their leaders (i.e., interpersonal justice), plays a significant role in reducing employee job burnout through the indirect effect of LMX quality. Interpersonal justice has been shown to be positively related to the quality of LMX (Cohen‐Charash & Spector, ; Cropanzano & Byrne, ; Scandura, ) and LMX has been shown to be negatively related to employee job burnout (Buunk & Schaufeli, ; Cordes, Dougherty & Blum, ; Hetland et al ., ). Our findings demonstrate that LMX is a critical relational mechanism underpinning the relationship between interpersonal justice and employee job burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support the assumption that the fairness perceptions of employees, particularly regarding treatment by their leaders (i.e., interpersonal justice), plays a significant role in reducing employee job burnout through the indirect effect of LMX quality. Interpersonal justice has been shown to be positively related to the quality of LMX (Cohen‐Charash & Spector, ; Cropanzano & Byrne, ; Scandura, ) and LMX has been shown to be negatively related to employee job burnout (Buunk & Schaufeli, ; Cordes, Dougherty & Blum, ; Hetland et al ., ). Our findings demonstrate that LMX is a critical relational mechanism underpinning the relationship between interpersonal justice and employee job burnout.…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘LMX’ refers to the quality of the supervisor–employee relationship and assumes that leaders tend to develop a unique relationship with each follower (Graen & Scandura, ; Graen & Uhl‐Bien, ; Schriesheim, Castro & Cogliser, ). Research has shown that employees' perception of justice facilitates the development of high‐quality LMX (Cohen‐Charash & Spector, ; Cropanzano & Byrne, ; Scandura, ). When individuals monitor the extent to which they are fairly treated by their leaders, they attempt to reciprocate to the sources of the perceived fairness (Gouldner, ).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…The high level of exchange is characterized by a high degree of mutual positive influence , loyalty, contributions, but also the obligation to exchange professional respect and trust, while otherwise low LMX quality is observed, often describing the conditions of the "outgroup" (Dienesch & Liden, 1986;Liden & Maslyn, 1998;Schriesheim et al, 1999). Different perceptions of justice are very important for the development of a quality relationship within the organization (Cropanzano & Byrne, 2000). If the shared obligations and trust came from justice, the result is a high level of LMX.…”
Section: Lmxmentioning
confidence: 99%
“…Hasil ini sangat berbeda dengan penelitian sebelumnya seperti Tekleab, Takeuchi, & Taylor, (2005); Cheung (2013); Chen & Jin (2014); Russell Cropanzano & Rupp (2016) yang telah menemukan POS sebagai pemediasi penuh terhadap hubungan keadilan distributif dan prosedural dengan OCBO.Demikan pula penelitian yang sebelumnya dilakukan oleh Robert H. yang menemukan bahwa keadilan prosedural merupakan anteseden terhadap POS, yang pada gilirannya sepenuhnya memediasi hubungannya dengan tiga dari empat dimensi OCB.Kemungkinan menarik yang dapat dipertimbangkan dari temuan ini adalah berkaitan dengan responden sebagai tenaga non regular ditambah lagi dengan masa kerja yang belum begitu lama di kampus. Faktor inilah yang menjadi masalah berkaitan dengan status mereka dan masa kerja yang belum menampilkan terbentuknya hubungan mereka dan kampus yang mempekerjakannya secara mendalam, sehingga tidak dapat mengharapkan peran ekstra yang ditujukan untuk organisasi dengan mengandalkan POS…”
Section: Posunclassified